PERILAKU KONSUMEN DALAM MEMAKAI JASA ONLINE PERSPEKTIF ETIKA ISLAM - MADYASARI, ARLUPI (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
In Islam, the purpose of consumption is not the concept of utility but benefit (maslahah). The achievement of maslahah is the aim of al-maqasidus-shariah. Consuming something with the intention to increase stamina to comply with Allah's commands, that makes consumption worth worship and gets a reward. The research method used by the author is to use a qualitative method which is a library research. That is, the author processes data from information sourced from books, journals, official websites. consumer behavior in using online services from the perspective of Islamic ethics is in accordance with Islamic ethics, has implemented monotheism (unity/unity) using online applications correctly does not violate Islamic rules. fair (equilibrium/fairness) using online applications as needed. Free will (free will) in an increasingly advanced era, humans must also follow these developments by utilizing current technology to shop online according to needs. Amanah (responsibility/responsibility) using online applications as well as possible does not violate Islamic rules. Halal because buying goods according to needs and halal in accordance with sharia principles. Simply put, in this case, it is in accordance with simple Islamic ethics because buying goods in a simple way is not excessive and maintaining assets in sufficient quantity and quality.